Scientism and philosophy. - Charlebois, Lise. (University of Ottawa (Canada), 1996)
The charge of scientism is appearing more frequently in recent academic journals, and in many contexts. It has been levelled against the founders of American sociology, who thought that sociology should model itself after the natural sciences. The developers of "systems theory" in political science are also accused of scientism because they want to apply the "theoretical and manipulative achievements and the mechanistic assumptions and procedures of the 'hard' physical sciences" to the traditional concerns of political science. Scientism is thought to involve the question of whether or not "the social and physical sciences are to be seen as similar on epistemological and methodological grounds". It is also thought to involve the mistaken idea that recourse to experimental method is always applicable and infallible. Again, scientism has been linked to evolutionary biology, structuralism, capitalism, modernity, and analytic philosophy. Those accused of being scientistic include Karl Marx, Sigmund Freud and W. O. Quine. Hilary Putnam has called scientism one of the most dangerous contemporary intellectual tendencies, and Peter Strawson says that the aim of philosophy is to abjure scientism. Conceptions of scientism differ among philosophers. In the following three chapters I will present three philosophical views on scientism and suggestions as to how it can be overcome. (Abstract shortened by UMI.)
Keywords: Sociology, Theory and Methods.